The Correlation Between Physical Activity Levels With Salivary Cortisol Levels on Medical Students, at Jenderal Soedirman University - Nugraha, Raffy Ave; Mustofa, Mustofa; Candrawati, Susiana; Sinensis, Rizki Amelia; Wulansari, Rahmawati (Medical and Health Journal, 2025)
Medical students generally have low levels of physical activity. Medical students also experience more severe stressors than students in other study programs. Salivary cortisol levels can reflect a person's stress level. This study aims to determine the correlation between physical activity levels and salivary cortisol levels in medical students at Jenderal Soedirman University. This study was conducted on 50 medical students at Jenderal Soedirman University aged 18–25 years. The study subjects were selected using purposive sampling. Physical activity levels were measured using the International Physical Activity Questionnaire-Long Form (IPAQ-LF), and saliva cortisol levels were measured using the Enzyme-Linked Immunosorbent Assay (ELISA) method. The correlation test used was Pearson's correlation test with a significance level of p<0.05. The results showed that the average physical activity level and saliva cortisol levels of the respondents were 1334.31±552.10 MET-minutes/week and 9.76±2.97 ng/mL. Bivariate analysis showed a p-value of 0.507, indicating that there was no correlation between physical activity levels and saliva cortisol levels among medical students at Jenderal Soedirman University.